Do doctors respond to financial incentive? : Evidence from the use of C-sections in the Czech Republic in the period 2004 – 2014 - Uhlík, Ondřej; Bertoli, Paola; Kalíšková, Klára; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2018)
Diagnoses Related Group system is used worldwide and still evolving. With many advantages brings several threats. One of them is a high share of Cesarean sections on a total number of child deliveries. This operation has many consequences for the child and the mother. Therefore, it should be done only in necessary cases, but many studies suggest otherwise. This phenomenon can be observed in many countries including the Czech Republic. This thesis agrees with the statement that C-sections are overused and tries to prove that there is a significant number of C-section operations performed unnecessarily as a consequence of obstetrician’s utility maximizing behavior.
Vedoucí práce: Paola Bertoli
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses